Level of alexithymia as a measure of personality dysfunction in avoidant personality disorder. (4th May 2021) - Simonsen, Sebastian; Eikenaes, Ingeborg Ullveit-Moe; Bach, Bo; Kvarstein, Elfrida; Gondan, Matthias; Møller, Stine Bjerrum; Wilberg, Theresa
Abstract: Background and objectives: Avoidant Personality Disorder (AvPD) is considered a mild to moderate personality disorder. However, few studies have focused on the heterogeneity of AvPD in terms of symptoms and severity. In the current study we set out to replicate and extend earlier findings showing that there is variation among patients with AvPD in terms of alexithymia and, further, that this variation is especially associated with specific facets of personality functioning and is not explained by measures of depression, symptom severity, or co-occurring personality disorder traits. Method: We used intake data from a sample of AvPD patients ( n = 56) who had been treated in similar outpatient services. Alexithymia was measured using the Toronto Alexithymia Scale (TAS-20). Patients filled out questionnaires that were analysed using linear regression models. Results and conclusions: Using well-established cut-off points for low, intermediate and high levels of alexithymia we found an almost equal distribution of alexithymia groups in our sample. Alexithymia was associated with higher personality dysfunction on twelve out of sixteen facets of personality functioning. For eight of these personality facets the alexithymia total score explained significant variance even after controlling for self-reported depression, symptom severity and clinician ratings of personality disorder. Results suggest that AvPD is heterogeneous and that alexithymia may be important as an indicator of severity of specific personality dysfunction.